Factors influencing financial behavior: The role of income as a moderator of financial knowledge - Nugroho Jati, Agustinus Kismet; Purwaningsih, Endang; Rahardani, Margareta Ernanda (Journal of Business & Banking, 2024)
The purpose of this study is to analyze the financial behavior of female MSME entrepreneurs, with income as a moderating variable. The data were collected by using a survey as the instrument in the form of a questionnaire. The respondents for this study were female MSME entrepreneurs residing in Solo and Yogyakarta, totaling 400 respondents, with 200 from each region. The distribution of the questionnaire was carried out offline and online via google form. The results indicate that financial knowledge and income do not influence financial behavior, while financial technology and lifestyle negatively affect financial behavior. Internal locus of control and spiritual intelligence positively impact financial behavior, with income which is not able to moderate the relationship between financial knowledge and financial behavior. These results have implications for the financial behavior of women who work as MSME entrepreneurs to improve their financial knowledge so that they become better and wiser in their financial behavior.